Paying to Avoid Recession: Using Reenlistment to Estimate the Cost of Unemployment - Mark Borgschulte; Paco Martorell (Institute for the Study of Labor (IZA), 2016)
This paper provides revealed-preference estimates of the monetary value of avoiding job search in a high-unemployment labor market by examining the behavior of military servicemembers deciding between reenlisting and exiting the military. We find that servicemembers would sacrifice 1.5-2% in earnings in exchange for avoiding a one percentage point increase in the home-state unemployment rate. Comparing these estimates to realized losses in post-service civilian earnings resulting from exiting the military during times of high unemployment suggests that mitigating factors (e.g., leisure, private and public transfers) offset less than one-third of the earnings losses caused by entering a weak labor market.
Keywords: J30; J60; J65; 330; welfare cost of business cycles; labor market entry; military reenlistment